Effects of various Fe compounds on the bioavailability of Pb contained in orally ingested soils in mice: Mechanistic insights and health implications. (December 2022) - Lin, Xin-Ying; Xue, Rong-Yue; Zhou, Lei; Zhang, Yao-Sheng; Wang, Hong-Yu; Zhang, Shuo; Li, Shi-Wei; Juhasz, Albert L.; Ma, Lena Q.; Zhou, Dong-Mei; Li, Hong-Bo
Graphical abstract: Highlights: Fe compounds applied to diets reduced soil Pb oral relative bioavailability variedly. EDTA-FeNa showed a better inhibition of Pb absorption. EDTA-FeNa at 100 mg Fe kg −1 in diet reduced Pb oral bioavailability from 79.5 to 23.1 %. Fe-Pb absorption competition and Pb urinary excretion with EDTA contributed to reduced Pb bioavailability. EDTA-FeNa may be the most appropriate supplement for intervention on human Pb exposure. Abstract: Reducing lead (Pb) exposure via oral ingestion of contaminated soils is highly relevant for child health. Elevating dietary micronutrient iron (Fe) intake can reduce Pb oral bioavailability while being beneficial for child nutritional health. However, the practical performance of various Fe compounds was not assessed. Here, based on mouse bioassays, ten Fe compounds applied to diets (100–800 mg Fe kg −1 ) reduced Pb oral relative bioavailability (RBA) in two soils variedly depending on Fe forms. EDTA-FeNa was most efficient, which reduced Pb-RBA in a soil from 79.5 ± 14.7 % to 23.1 ± 2.72 % (71 % lower) at 100 mg Fe kg −1 in diet, more effective than other 9 compounds at equivalent or higher doses (3.6–68 % lower). When EDTA-FeNa, ferrous gluconate, ferric citrate, and ferrous bisglycinate were supplemented, Fe-Pb co-precipitation was not observed in the intestinal tract. EDTA-FeNa, ferrous gluconate, ferric citrate, and ferrous sulfate suppressed duodenal divalent metal transporter 1 (DMT1)mRNA relative expression similarly (27–68 % lower). In comparison, among ten compounds, EDTA-FeNa elevated Fe concentrations in mouse liver, kidney, and blood (1.50–2.69-fold higher) most efficiently, suggesting the most efficient Fe absorption that competed with Pb. In addition, EDTA was unique from other organic ligands, ingestion of which caused 12.0-fold higher Pb urinary excretion, decreasing Pb concentrations in mouse liver, kidney, and blood by 68–88 %. The two processes (Fe-Pb absorption competition and Pb urinary excretion with EDTA) interacted synergistically, leading to the lowest Pb absorption with EDTA-FeNa. The results provide evidence of a better inhibition of Pb absorption by EDTA-FeNa, highlighting that EDTA-FeNa may be the most appropriate supplement for intervention on human Pb exposure. Future researches are needed to assess the effectiveness of EDTA-FeNa for intervention on human Pb exposure.